Efeitos da suplementação de óleo de coco babaçu na fadiga de mulheres com neoplasia mamária - PEREIRA, Paula Tâmara Vieira Teixeira (2018)
Introduction: Fatigue is the most commonly reported symptom of cancer patients that may be present prior to antineoplastic therapy, however please increase during treatment. The prevalence of this symptom is estimated in 25% to 99% of the patients, being incapacitating mainly in cases where there is metastasis. Objective: Evaluate the effect of babassu coconut oil supplementation on fatigue, quality of life, depression, inflammatory markers and immunological markers in breast cancer patients. Methods: Randomized clinical trial with 44 patients with breast cancer undergoing antineoplastic treatment. The patients were divided into three groups: group babaçu (GB), coconut oil group (COG) and control group (CG). The GB recommendation of babassu oil, the COG ordering of coconut oil and the GC that is not a requested supplementation. The variables analyzed were fatigue by Piper-Fatigue Scale, quality of life by EORTH QLQ- 30, depression by Beck Depression Inventory, TNF-α, IL-6 and salivary IgA. Results: There was a reduction on fatigue score in GB, on both total score and behavioral and affective dimension in relation to COG and CG. Quality of life had improved on the functional scale in GB. There was no significant change in depression in either group evaluated. There was a increase of TNF-α in COG and CG, not observed in GB, but there was a decrease in IL-6 in GB. IgA increased in GB and COG and decreased in GC. Conclusions: Babassu oil supplementation was effective in reducing total, behavioral and affective fatigue, improving behavioral quality of life and reducing IL-6 levels and increasing IgA levels after 12 weeks of intervention.